2010
DOI: 10.3109/08958378.2010.487549
|View full text |Cite
|
Sign up to set email alerts
|

Variation in echocardiographic and cardiac hemodynamic effects of PM and ozone inhalation exposure in strains related toNppaandNpr1gene knock-out mice

Abstract: Elevated levels of ambient co-pollutants are associated with adverse cardiovascular outcomes shown by epidemiology studies. The role of particulate matter (PM) and ozone (O3) as co-pollutants in this association is unclear. We hypothesize that cardiac function following PM and O3 exposure is variably affected by genetic determinants (Nppa and Npr1 genes) and age. Heart function was measured before and after 2 days each of the following exposure sequence; (1) 2-h filtered air (FA) and 3-h carbon black (CB; 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…Thus, declines in both EjeT and CtrI suggested that PEPs exposure may impair contractility despite HRV indicating enhanced sympathetic influence. These findings accord with the negative inotropic effects of exposures at > 2-fold higher PM concentrations of carbon black [33,34], diesel exhaust [31], or concentrated ambient PM [69], which may decrease cardiac output while inducing catecholamine surges to provoke hypertension, pulmonary edema, and intracellular signaling toward cardiac remodeling [65]. Accordingly, PEPs impaired contractility indices during exposure especially on day 21, but these effects rapidly dissipated immediately after exposure when systolic pressure increased-potentially through neurohormonal compensation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, declines in both EjeT and CtrI suggested that PEPs exposure may impair contractility despite HRV indicating enhanced sympathetic influence. These findings accord with the negative inotropic effects of exposures at > 2-fold higher PM concentrations of carbon black [33,34], diesel exhaust [31], or concentrated ambient PM [69], which may decrease cardiac output while inducing catecholamine surges to provoke hypertension, pulmonary edema, and intracellular signaling toward cardiac remodeling [65]. Accordingly, PEPs impaired contractility indices during exposure especially on day 21, but these effects rapidly dissipated immediately after exposure when systolic pressure increased-potentially through neurohormonal compensation.…”
Section: Discussionsupporting
confidence: 69%
“…Exposures to PM aerosols can impair LV systolic performance, indicated by decreases in ejection fraction, fractional shortening, and-assuming unaltered systolic and diastolic pressures-maximum LV pressure slope (dP/dt max ) [31][32][33][34][35]. Declines in these markers, along with LV ejection time [36,37] and contractility index (pressure-normalized dP/dt max ) [35], reflect diminished LV contractility and can denote heart failure: an inability of the LV to perfuse vital tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Toxicologic studies have reported differences in effects after O 3 exposure among different inbred strains of mice, which indicates that genetic background contributes to differential risk (Chuang et al 2009; Hamade and Tankersley 2009; Hamade et al 2008; Tankersley et al 2010). Inbred strains have been used in genetic linkage and genome-wide association studies to identify candidate genes that lead to increased risk (Cho and Kleeberger 2007), and additional studies have been conducted to validate these candidate genes and other related genes, primarily using mice with targeted gene deletions.…”
Section: Resultsmentioning
confidence: 99%
“…Toxicologic studies have also shown that oxidative damage and stress may be higher after O 3 exposure in young compared with adult rodents (Fortino et al 2007; Servais et al 2005). In addition, a series of studies reported an association between O 3 exposure and bradycardia that was present among young but not older mice (Hamade et al 2010; Hamade and Tankersley 2009; Tankersley et al 2010). Physiologic changes specific to older adults that have been observed in toxicologic studies include changes in heart structure (i.e., ventricular posterior wall thickness at end systole) (Tankersley et al 2010), wound closure (Lim et al 2006), and neurodegenerative diseases (as measured by higher lipid peroxidation in the hippocampus) (Rivas-Arancibia et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…As such, the type of cardiac responses following air pollution may be dependent on the type of pollutant, or combination of pollutants, with some degree of overlapping effects. Tankersley et al [ 44 ] showed that both carbon black particles and O 3 caused reduced cardiac output in mice but due to two different mechanisms. Thus, we speculate that although both particles and gases produce similar cardiac decrements, the mechanisms mediating the response may not be the same (e.g.…”
Section: Discussionmentioning
confidence: 99%